The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11119-017-9548-z
|View full text |Cite
|
Sign up to set email alerts
|

A geospatial variable rate irrigation control scenario evaluation methodology based on mining root zone available water capacity

Abstract: Increasing concern for sustainable water use has the agriculture industry working toward higher efficiency in use of irrigation water. Recent advancements have improved the capabilities of center pivot irrigation systems to vary water application depths across the field, a technology known as variable rate irrigation (VRI). The goal of this study was to provide a geospatial method for potential VRI technology adopters to evaluate control scenarios and potential water savings using freely available datasets. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Some companies provide the ability to control zones of sprinklers, while others can control each sprinkler independently [46]. Currently, it is possible to achieve sector control with very small resolution, and zone control can add irrigation zones further to the sector at the small scales of lateral spans ( Figure 1) [48]. A study conducted in Canada to evaluate the performance of VRI found that the accuracy of water application was up to 90% in the center pivot system [49].…”
Section: Variable-rate Irrigation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some companies provide the ability to control zones of sprinklers, while others can control each sprinkler independently [46]. Currently, it is possible to achieve sector control with very small resolution, and zone control can add irrigation zones further to the sector at the small scales of lateral spans ( Figure 1) [48]. A study conducted in Canada to evaluate the performance of VRI found that the accuracy of water application was up to 90% in the center pivot system [49].…”
Section: Variable-rate Irrigation Technologiesmentioning
confidence: 99%
“…At a large scale, water pumpage and use can be reduced by adopting VRI. A geospatial method has been provided for potential VRI technology adopters to achieve potential water savings in the field using freely available datasets such as soil survey data from the Natural Resources Conservation Service (NRCS) [48]. In this study, the difference in application depth between conventional irrigation and VRI was estimated based on root zone available water capacity.…”
Section: Impact Of Variable-rate Irrigationmentioning
confidence: 99%
“…The field size was nearly 53 ha. Further details about the field can be found in Miller et al (2017) and Barker et al (2018b).…”
Section: Study Sitementioning
confidence: 99%
“…Spatial patterns in AWC can be characterized with electrical conductivity (Hedley and Yule, 2009;Evans et al, 2013;Vanella et al, 2019) or other hydrogeophysical datasets (Finkenbiner et al, 2018). Differences in AWC of a field could be used to compute VRI prescriptions, which may result in reductions in energy usage and water withdrawals (Miller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has justified the use of precision irrigation through modelling to establish scheduling of irrigation by management zones (Haghverdi et al, 2015;Ceresoli et al, 2016;Miller et al, 2018 . For anhydrous ammonia application, Bora et al (2005) On the development of zone control technologies, and proposed prototypes of sprinklers for centre pivots or linear-move systems.…”
Section: Introductionmentioning
confidence: 99%